Household Transmission of Ebola Virus: Risks and Preventive Factors, Freetown, Sierra Leone, 2015. (6th April 2018) - Reichler, Mary R; Bangura, James; Bruden, Dana; Keimbe, Charles; Duffy, Nadia; Thomas, Harold; Knust, Barbara; Farmar, Ishmail; Nichols, Erin; Jambai, Amara; Morgan, Oliver; Hennessy, Thomas; et al.
Abstract : Of household contacts of Ebola cases, 9.9% developed Ebola. Risk factors for transmission included providing care to the case, case death in the house, and no reported fever in the case. Behaviors adopted to avoid contact with the case were protective. Abstract: Background: Knowing risk factors for household transmission of Ebola virus is important to guide preventive measures during Ebola outbreaks. Methods: We enrolled all confirmed persons with Ebola who were the first case in a household, December 2014–April 2015, in Freetown, Sierra Leone, and their household contacts. Cases and contacts were interviewed, contacts followed prospectively through the 21-day incubation period, and secondary cases confirmed by laboratory testing. Results: We enrolled 150 index Ebola cases and 838 contacts; 83 (9.9%) contacts developed Ebola during 21-day follow-up. In multivariable analysis, risk factors for transmission included index case death in the household, Ebola symptoms but no reported fever, age <20 years, more days with wet symptoms; and providing care to the index case ( P < .01 for each). Protective factors included avoiding the index case after illness onset and a piped household drinking water source ( P < .01 for each). Conclusions: To reduce Ebola transmission, communities should rapidly identify and follow-up all household contacts; isolate those with Ebola symptoms, including those without reported fever; and consider closer monitoring of contacts who provided care to cases. Households could consider efforts to minimize risk by designating one care provider for ill persons with all others avoiding the suspected case.